(untitled) (International Journal of Biology and Chemistry, 2016)
Catalysts on metal block carriers were prepared and used in laboratory tests and in the conditions of actual operation. Stability of the carrier and the active phase of the catalysts to poisoning by water vapour was examined. Such poisoning of catalysts promoted with Pt is reversible and the catalysts are again activated by heating at T = 300oC under a stream of dry air for 4 h. The experiments by defining of possibility of interaction of NO with the soot supported on the block catalysts was investigated. Full-size catalyst samples were tested at the diesel engine – generator of Kama Automobile Plant truck running on diesel fuel and at the stand on the basis of diesel generator capacity of 4 Kv. Application the catalytic neutralizer of the fulfilled gases resulted in decrease in harmful emissions in comparison with the engine without neutralizer: in case of Kama Automobile Plant on a mode of the minimal idling (800 rev./min.) efficiency of neutralizer has made on NOx-59.0 %, CxHy-86.0%, CO-99.0%; in case of a stand a degree of cleaning from CO was 100%, hydrocarbons – 99.0%, nitrogen oxides – 61.9%.